Thinking in opposites improves hypothesis testing performance in Wason's rule-discovery task. - Branchini, Erika; Bianchi, Ivana; Burro, Roberto (Memory & Cognition, 2025)
We investigate whether hypothesis testing can be improved by a simple prompt to "think in opposites," a strategy suggested by a growing body of literature as being beneficial in various reasoning and problem-solving contexts. We employed Wason's rule-discovery task and designed three experimental conditions: training that prompted an analysis of the properties characterizing the initial seed triple, training that prompted the same analysis but subsequently required the identification of the opposites of each property for use in the testing phase, and a no-prompt condition. Thinking in opposites nearly doubled the success rate and led to a more frequent discovery of the rule on the first attempt. This improved efficacy was due not to the testing of more triples but to less reiteration of the same hypothesis and a greater awareness of the ascending-descending critical dimension. We discuss how thinking in opposites appears to stimulate counterfactual thinking, with respect to previous literature.